2020
DOI: 10.1097/pts.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Patient Safety Events Occurring in the Emergency Department

Abstract: The aim of the study was to describe and analyze the risk factors associated with patient safety events (PSEs), defined as adverse events (AEs), preventable AEs (PAEs), and near-miss events (NMEs), in the emergency department (ED). Methods:It was a retrospective cohort study using ED patients' data retrieved from January 2010 to December 2016. Quality assurance issues (QAIs) used as triggers included the following: issues during procedural sedation, death within 24 hours of admission, patients' and physicians'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…A containment of LOS times and an improvement in the outcome of some categories of patients was observed as well [81][82][83][84][85][86][87][88]. These findings were in line with data from several other European and American research groups [89][90][91][92][93][94].…”
Section: Microlevel Strategiessupporting
confidence: 81%
“…A containment of LOS times and an improvement in the outcome of some categories of patients was observed as well [81][82][83][84][85][86][87][88]. These findings were in line with data from several other European and American research groups [89][90][91][92][93][94].…”
Section: Microlevel Strategiessupporting
confidence: 81%
“…The ED represents the principal entrance into the hospital healthcare delivery system. Healthcare in the ED has a unique nature, complexity and urgency (Alsabri et al, 2022b). The performance of the ED plays a critical role in decreasing mortality rates and protecting public health, and in public satisfaction with medical services in general (Trzeciak and Rivers, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is crucial as poor staffing/understaffing has been implicated in poor and adverse patient outcomes by a multitude of studies, so it is not surprising that hospitals have the consistent perception of poor staffing negatively affecting patient safety. It of course follows that with improved staffing, patient safety would congruently improve [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly attributable to the fact that studies have shown that punitive responses to errors are the main obstacle for disclosure of errors once they are identified [ 1 - 24 ]; a possible remedy to which is to establish a just culture [ 24 ] that recognizes errors as system failures rather than individual failures and encourages the staff to report events without fear of blame is essential for better error identification and continuous improvements. Patient safety improvements can only occur in learning organizations where preventive measures are taken after adverse events and near misses are identified, reported, and analyzed [ 25 ]. Therefore, under-reporting of events can hinder organizational improvement specifically regarding patient safety.…”
Section: Discussionmentioning
confidence: 99%